Micro(structure) before macro? The predictive power of aggregate illiquidity for stock returns and economic activity - Chen, Yong; Eaton, Gregory W.; Paye, Bradley S. (Journal of Financial Economics, 2018)
This paper constructs and analyzes various measures of trading costs in US equity markets covering the period 1926–2015. These measures contain statistically and economically significant predictive signals for stock market returns and real economic activity. We decompose illiquidity proxies into a component capturing aggregate volatility and a residual. The predictive content of these components differs in important ways. Specifically, we find strong evidence that the component of illiquidity uncorrelated with volatility forecasts stock market returns. Both the volatility and residual components of illiquidity contain information regarding future economic activity.